Development of alternative plant-based culture media using cactus pear cladodes for oyster mushroom (Pleurotus ostreatus) growth - Ashenafi Teklay Yaekob; Etsay Mesele; Tesfakiros Semere; Teklehaimanot Fisseha Gebremichael; Melaku Mekonen Kasegn; Girmay Mekonen Gebrewahid; Haregot Fissha (Discover Applied Sciences)
Abstract In Tigray, Ethiopia, the mushroom-growing industry is new and has been introduced as an alternative to ensure sustainable food and nutrition security and create employment opportunities. The culture medium used for the growth of mushroom tissue culture and spawn preparation generally uses potato dextrose agar (PDA) media, but since the price is high, it is necessary to find alternative media and spawn substrates using locally available materials. The objective of this study was to produce readily available and reasonably priced an alternative cladode of Opuntia ficus-indica culture medium for the mycelial growth of Pleurotus ostreatus. Thus, three formulated cactus pear cladode agars (CPCAs) with concentrations of 40, 20, and 13.33 g/L and PDA (control) were used. Chemical composition analysis of the CPCA revealed the presence of carbohydrates (39.54 ± 0.09%), crude fiber (26.25 ± 0.35%), ash (5.32 ± 0.11%), crude protein (18.93 ± 0.01%), and moisture (6.09 ± 0.16%). A larger mycelial diameter (7.97 ± 0.21 cm) and growth rate (1.59 ± 0.04 cm/day) occurred on CPCA (40 g/L) at PDA, in which the mycelial growth diameter and growth rate were found to be 6.32 ± 1.03 cm and 1.15 ± 0.01 cm/day, respectively, after 5 days of measurement. A similar mycelial density on CPCA (40 g/L) and PDA media was observed after 8 days of incubation. Similar mycelial growth was observed on sorghum (the control) and sliced dry cladodes of cactus pear (alternative) after 16 days of incubation. Generally, CPCA (40 g/L) can potentially serve as an inexpensive, locally available alternative medium to grow oyster mushrooms.